2008
DOI: 10.1080/10398560701616213
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder Symptoms in the Files of Australian Servicemen Hospitalized in 1942–1952

Abstract: PTSD symptoms may have been common during and after World War II. At that time avoidance was not considered a symptom of disorder. Intrusive and arousal symptoms may be the core symptoms of PTSD and avoidance symptoms need to be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These findings are consistent with previous studies of veteran and civilian samples, which found that partial PTSD is associated with an intermediate level of impairment relative to no PTSD and full PTSD. [4,6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22] They also extend previous research on OEF/OIF veterans [1][2][3] to suggest that full PTSD is associated with health and psychosocial difficulties. Because partial PTSD is not a diagnostic classification and may not be routinely identified as part of PTSD screenings, clinicians may underestimate the magnitude of impairment associated with partial PTSD in OEF/OIF veterans, which may decrease mental-health treatment seeking in this population, negatively affect health and psychosocial functioning, and delay successful reintegration into civilian life.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings are consistent with previous studies of veteran and civilian samples, which found that partial PTSD is associated with an intermediate level of impairment relative to no PTSD and full PTSD. [4,6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22] They also extend previous research on OEF/OIF veterans [1][2][3] to suggest that full PTSD is associated with health and psychosocial difficulties. Because partial PTSD is not a diagnostic classification and may not be routinely identified as part of PTSD screenings, clinicians may underestimate the magnitude of impairment associated with partial PTSD in OEF/OIF veterans, which may decrease mental-health treatment seeking in this population, negatively affect health and psychosocial functioning, and delay successful reintegration into civilian life.…”
Section: Discussionmentioning
confidence: 73%
“…[6] Although partial PTSD is not a formal diagnosis, it has been used in research to characterize survivors who report clinically significant trauma-related symptoms but who do not meet full diagnostic criteria for PTSD. [7] Partial PTSD is identified when an individual meets criteria for cluster B (re-experiencing) and criteria for either cluster C (avoidance) or cluster D (arousal), or if they met criteria for cluster B and endorsed at least one symptom from cluster C and one from cluster D. [6,8] Studies of partial PTSD in veterans, [6,[8][9][10][11][12] ambulance workers, [13] and survivors of toxic chemical exposures, disasters, and other traumas [14][15][16][17][18][19][20][21][22] have found intermediate levels of psychosocial impairment and quality of life relative to individuals without PTSD and those with full/threshold PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, because partial PTSD is not a diagnosis in DSM-IV, it may easily be missed or ignored in clinical and research settings. However, partial PTSD is associated with significant psychosocial impairment (Berger et al, 2007; Favaro et al, 2006; Friedman et al, 1997; Grubaugh et al, 2005; Jakupcak et al, 2007; Kulka, 1990; Pietrzak et al, 2009; Schnurr et al, 2000; Watson & Daniels, 2008), and increased prevalence of Axis I disorders (Jeon et al, 2007; Pietrzak et al, under review). The present study extends these findings to suggest that partial PTSD is also associated with elevated rates of borderline, schizotypal, and narcissistic PDs, and in women, antisocial PD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of partial PTSD in various trauma-exposed populations have found intermediate levels of psychiatric comorbidity and functional impairment relative to trauma controls and individuals with full PTSD (Berger et al, 2007; Favaro et al, 2006; Friedman et al, 1997; Grubaugh et al, 2005; Jakupcak et al, 2007; Kulka, 1990; Pietrzak et al, 2009; Schnurr et al, 2000; Watson & Daniels, 2008). To our knowledge, however, only 1 study has examined personality characteristics of individuals with partial PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Partial PTSD is typically identified when affected individuals meet Criterion B (re-experiencing) and either Criterion C (avoidance and numbing) or D (arousal), or if they meet Criterion B and endorse at least one symptom each from Criteria C and D (Kulka, 1990; Schnurr, Ford, Friedman, Green, Dain, & Sengupta, 2000). Studies of partial PTSD in veterans (Favaro, Tenconi, Colombo, & Santonastaso, 2006; Grubaugh, Magruder, Waldrop, Elhai, Knapp, & Frueh, 2005; Jakupcak, Conybeare, Phelps, Hunt, Holmes, Felker, Klevens, & McFall, 2007; Kulka, 1990; Pietrzak, Goldstein, Malley, Johnson, & Southwick, 2009; Schnurr et al, 2000; Watson & Daniels, 2008), ambulance workers (Berger, Figueira, Maurat, Bucassio, Vieira, Jardim, Coutinho, Mari, & Mendlowicz, 2007), and survivors of toxic chemical exposures, disasters, and other traumas (Adams, Boscarino, & Galea, 2006; Berger et al, 2007; Breslau et al, 2004a; Jeon et al, 2007; Lai, Chang, Connor, Lee, & Davidson, 2004; Marshall, Olfson, Hellman, Blanco, Guardino, & Struening, 2001; Pietrzak, Goldstein, Southwick, & Grant, in press; Schutzwohl & Maercker, 1999; Stein, Walker, Hazen, & Forde, 1997; Zlotnick, Franklin, & Zimmerman, 2002) have found intermediate levels of psychiatric comorbidity and functional impairment compared to trauma-exposed individuals without PTSD and those with full PTSD. Partial PTSD can persist for years (Jeon et al, 2007; Schnurr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%